OC-016 Liraglutide is effective in the histological clearance of non-alcoholic steatohepatitis in a multicentre, double-blinded, randomised, placebo-controlled phase ii trial. (22nd June 2015) - Armstrong, MJ; Gaunt, P; Aithal, GP; Parker, R; Barton, D; Hall, D; Guo, K; Abouda, G; Aldersley, M; Gough, SC; Tomlinson, JW; Brown, R; et al.
Abstract : Introduction: There are still no licensed therapies for non-alcoholic steatohepatitis (NASH). Glucagon-like peptide-1 (GLP-1) analogues are licensed in type 2 diabetes, and are promising therapeutic candidates for NASH, yet no trial data exists on their efficacy in this setting. The histological efficacy and safety of the long-acting GLP-1 analogue, liraglutide, was assessed in patients with NASH. Method: In the Liraglutide Efficacy and Action in NASH (LEAN) trial (ClinicalTrials.gov NCT01237119 ) overweight patients with biopsy-confirmed NASH were randomised (1:1) to receive 48-weeks treatment with once-daily, subcutaneous injections of either 1.8 mg liraglutide or liraglutide-placebo (control). Randomisation was stratified by trial centre (n = 4) and diabetes status. The primary outcome measure as assessed centrally by two independent histopathologists (RMB, SGH) was improvement in liver histology, defined as 'resolution of definite NASH' and no worsening in fibrosis from baseline to end-of-treatment (EOT). Preliminary analyses were performed by intention-to-treat. Results: Of the 52 patients randomised (mean age 51 years, 60% male, 33% type 2 diabetes, 52% F3/F4 Kleiner fibrosis stage), 45 patients underwent EOT liver biopsies. The primary end-point was met, and 9 (39%) of 23 patients on liraglutide had resolution of definite NASH compared to 2 (9%) of 22 patients on placebo (p = 0.019). Only 2 (9%) patients on liraglutide had worsening of fibrosis compared to 8 (36%) on placebo (p = 0.026). Moreover, liraglutide reduced weight (–5.3 vs. –0.6 kg, p = 0.001), BMI (–1.8 vs. –0.3 kg/m 2, p = 0.003), and fasting glucose (–1.0 vs –0.7 mmol, p = 0.005) compared to placebo. Reductions in ALT (–27 vs. –10, p = 0.126) and HbA1c (–0.5% vs. –0.03, p = 0.07) were also seen with liraglutide, albeit not significant versus placebo. There were no treatment differences in lipid profile or systolic BP. There were no serious adverse events in patients on liraglutide, which was well-tolerated with only 2 (8%) of 26 patients withdrawing from treatment due to drug-related gastro-intestinal (nausea, diarrhoea) side effects. Conclusion: In a randomised controlled trial liraglutide met the primary end-point of histological clearance of NASH, and a reduction in progression of fibrosis. It was also safe and well-tolerated. Phase III registration trials are now warranted for GLP-1 therapy in patients with NASH. Disclosure of interest: M. Armstrong Grant/ Research Support from: Novo Nordisk – free drug for the trial, P. Gaunt: None Declared, G. Aithal: None Declared, R. Parker: None Declared, D. Barton: None Declared, D. Hall: None Declared, K. Guo: None Declared, G. Abouda: None Declared, M. Aldersley: None Declared, S. Gough Grant/ Research Support from: Novo Nordisk, Speaker Bureau of: Novo Nordisk, J. Tomlinson: None Declared, R. Brown: None Declared, S. Hubscher: None Declared, P. Newsome Grant/ Research Support from: Novo Nordisk – free drug for the trial, Speaker Bureau of: Novo Nordisk.